2001
DOI: 10.1292/jvms.63.11
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Gastrin-Releasing Peptide in the Bovine Uterus and Placenta.

Abstract: ABSTRACT. Gastrin-releasing peptide (GRP), a mammalian homologue of amphibian bombesin, has been suggested to be a novel regulatory peptide in the reproductive tract during pregnancy. In this study, the localization of GRP in the bovine uterus and placenta was demonstrated by immunohistochemistry. Uterine and placental samples were collected from nonpregnant and pregnant specimens, respectively. Tissue sampling was done from the caruncle and intercaruncle of the uterus, and from the placentome (caruncle and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…The abundance of the gastrin-releasing peptide (GRP) mRNA was 4-fold higher at oestrus than at dioestrus. GRP belongs to a group of regulatory peptides and was found to be expressed in the reproductive tract of different species (Happola & Lakomy 1989, Fraser et al 1994, Whitley et al 1996, Budipitoj et al 2001. In sheep a study of GRP mRNA expression during the oestrous cycle in the uterus showed that expression was markedly increased at day 16 compared with days 4, 10, 12 and 14 (Whitley et al 1998); day 0 was not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of the gastrin-releasing peptide (GRP) mRNA was 4-fold higher at oestrus than at dioestrus. GRP belongs to a group of regulatory peptides and was found to be expressed in the reproductive tract of different species (Happola & Lakomy 1989, Fraser et al 1994, Whitley et al 1996, Budipitoj et al 2001. In sheep a study of GRP mRNA expression during the oestrous cycle in the uterus showed that expression was markedly increased at day 16 compared with days 4, 10, 12 and 14 (Whitley et al 1998); day 0 was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In sheep a study of GRP mRNA expression during the oestrous cycle in the uterus showed that expression was markedly increased at day 16 compared with days 4, 10, 12 and 14 (Whitley et al 1998); day 0 was not investigated. The expression in the uterus was located mainly to the uterine gland epithelial cells (Budipitoj et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Sections were examined with a c o n v e n t i o n a l l i g h t m i c r o s c o p e , a n d photomicrographs were taken with a digital camera. * Crown-rump-length of fetus, Intensity of immunoreactivities: -, not detected; ±, very weak; +, weak; ++, moderate, The strong intensity (+++) of GRP immunoreactivity was deduced from the previous report of GRP immunolocalization in the uterine gland of pregnant cow [29].…”
Section: In Situ Hybridizationmentioning
confidence: 90%
“…G R P immunoreactivity has also been detected in the superficial epithelial cells of the intercotyledonary endometrium of sheep [26], the trophoblast, t ro p ho bl as ti c gian t c ell s, h ybr id c ell s and superficial epithelial cells of the caruncle of the cow [29]. Furthermore, since GRP mRNA is expressed only at day 16 in the estrous cycle of sheep, it was suggested that the appearance of GRP in uterine gland cells depends on the stage of the estrous cycle [31].…”
mentioning
confidence: 98%
See 1 more Smart Citation